Le arti amanti invenzione a due voci - Luzi, Mario 1914-2005; Sampaoli, Luciano 1955- (Medusa, 2008)
Accompanying CD contains ... "4 Lieder per soprano e pianoforte. Angela Battaglia, soprano; Nunzio Dello Iacovo, pianoforte."--CD label. Also contains a track of the poet reading the words of one of the Lieder.
Incl. (p. 111-147) scores. - Also cont. (p. 82-105) 2 interviews, 1 with M. Luzi, poet, 1 with L. Sampaoli (1955-), composer. - Contains bibliography, bibliographical references and notes
Keywords: Luzi, Mario -- Torre delle ore; Luzi, Mario -- Criticism and interpretation; Sampaoli, Luciano -- Criticism and interpretation; Sampaoli, Luciano -- 1955- -- Torre delle ore; Luzi, Mario -- 1914-2005; Sampaoli, Luciano -- 1955-